Styrene hydroformylation catalyzed by rhodium supported molybdenum disulphide - Pitínová, Martina; Krnáčová, Alica; Shafiq, Ayesha; Danylo, Iryna; Koláčný, Lukáš; Veselý, Martin (Catalysis today, 2025)
This study addresses the challenge of developing heterogeneous catalysts for olefin hydroformylation—a process traditionally dominated by homogeneous rhodium complexes that, while highly efficient, pose challenges in separation and recycling, limiting their sustainability. To overcome these limitations, we investigated rhodium-based catalysts supported on MoS2. While heterogeneous systems typically exhibit lower activity and selectivity, they offer advantages in recyclability and process integration. We synthesized and characterized Rh/MoS2 catalysts and evaluated their performance in styrene hydroformylation. The effects of preparation methods (conventional, modified, and microwave-assisted impregnation) and rhodium loading (0.5–10 wt%) on structural and catalytic properties were investigated. Characterization techniques included X-ray fluorescence, X-ray diffraction, nitrogen physisorption, and scanning and transmission electron microscopies. Catalysts prepared via wet impregnation with 0.5–6 wt% Rh exhibited small, highly dispersed rhodium species that remained stable under reaction conditions up to 3 wt% Rh. These Rh species were located on the external surface of the non-porous MoS2 support, ensuring accessibility without diffusion limitations. The best-performing catalyst achieved aldehyde selectivity of 80–86 %, comparable to the homogeneous Wilkinson catalyst, with a maximum styrene conversion of 28 % observed for the 2 wt% Rh/MoS2 catalyst prepared at 80 °C. Catalyst reuse was also explored, revealing changes in product distribution and activity upon recycling—suggesting surface or structural evolution during operation. These findings provide a foundation for further optimization and highlight the potential of MoS2-supported Rh catalysts as viable heterogeneous alternatives for hydroformylation processes. [Display omitted] •Developed Rh/MoS₂ catalysts for olefin hydroformylation with 80–86% aldehyde selectivity.•Investigated the effect of preparation methods and Rh loading (0.5–10 wt%) on catalyst structure and performance.•Employed comprehensive characterization techniques including XRF, XRD, nitrogen physisorption, SEM, and TEM.•Reached a styrene conversion of 28 % with 2 wt% Rh/MoS2 with 82 % selectivity toward desired aldehydes.•Highlighted the potential of MoS2-supported Rh catalysts for efficient and recyclable hydroformylation.